Design and Creation of Four-wheel Non- interaction Navigation Machinery - Vikas Ranjan; Alapan Chatterjee; A. Harsha Vardhan; K. Ramakrishna; B. Anand (International Journal of Machine Systems and Manufacturing Technology, 2023)
Here we are trying to improve the steering mechanism, by rotating all 4-wheels to reduce the radius of rotation. This is a Mechatronics based project where different sensors and actuators has to employed. Electronic controller unit is going to be act as the vital element of this project through which the complete steering system has to be controlled. This electronic controller receives analog signal from the user and convert it into digital signal as an output. Through this project we would like to illustrate various modes of steering working behavior which will finally cause the vehicle to run under complete control of the user. “Two-wheel steering mechanism, four-wheel high-speed steering mechanism and four-wheel low speed steering mechanism” are few most commonly used mechanisms these days. These discrete modes of steering working mechanism are possible because of independent motors are going to be used here. Using various electrical, mechanical and electronics elements, we could get able to design and fabricate this 4-wheel noncontact steering mechanism.
Keywords: Actuator; Electronic controller; Wheel; sensor; steering mechanism